Promoting equity in breastfeeding through peer counseling: the US Breastfeeding Heritage and Pride program - Elizabeth C Rhodes; Grace Damio; Helen Wilde LaPlant; Walter Trymbulak; Carrianne Crummett; Rebecca Surprenant; Rafael Pérez-Escamilla (BMC, 2021)
Abstract Background In the United States, Black and Hispanic mothers have lower breastfeeding rates compared with White mothers. To address breastfeeding inequities, the Breastfeeding Heritage and Pride program (BHP) provides breastfeeding support for predominately low-income minority mothers in Connecticut and Massachusetts. We described the process of designing BHP, the program model, and its impact on breastfeeding outcomes. Methods This BHP case study is based on in-depth interviews with BHP designers and implementers, peer counselors, and clients; a literature review of BHP impact evaluation studies; and a review of BHP materials. To guide the analysis and organize results, we used the Community Energy Balance Framework, an equity-oriented, multi-level framework for fostering healthy lifestyles. Results The Hispanic Health Council designed BHP to address barriers to breastfeeding identified through formative qualitative research with the Latino community, namely lack of role models, limited social support, embarrassment when breastfeeding in public, lack of breastfeeding knowledge, and a norm of formula feeding. According to the BHP model, clients receive education and support through in-person home and hospital visits supplemented by phone calls, beginning prenatally and continuing through one year postpartum. Counseling is delivered by peer counselors, women who have successfully breastfed, have similar cultural roots and life experiences as the clients they serve, and have completed intensive training on lactation management and communication skills. International Board Certified Lactation Consultants provide clinical guidance and ongoing training to peer counselors, as well as direct support to clients, if more specialized knowledge and clinical expertise is needed. Clients facing housing and food insecurity or other socio-economic obstacles that may negatively influence breastfeeding and health and well-being more broadly are connected to other health and social services needed to address their social determinants of health needs, including health care access and food and rent assistance programs. To continuously improve service delivery, BHP has a robust monitoring and evaluation system. In two randomized-controlled trials, BHP was shown to improve breastfeeding initiation and duration of any and exclusive breastfeeding. Conclusions BHP highlights the importance of community-engaged formative research for informing breastfeeding program design. It also provides an evidence-based example of a program model that offers a continuum of breastfeeding support, considers cultural-contextual influences on breastfeeding and social determinants of health, and incorporates continuous quality improvement.